Research Progress on Sugar Signaling during Fruit Development and Ripening - Libin WANG; Junpeng NIU; Guodong WANG; Yuhua XIE; Chen ZHANG; Zhifang YU; Bing XIE; Qiuqin ZHANG; Heyun ZHENG; Ruihong YUAN; Xinli GENG; Shaoling ZHANG (Guangdong nongye kexue)
Sugar is extremely important for the growth and development of fruits, and it is also vital for the improvement of fruit quality. In addition, its content, species, and proportion determine the sweetness and flavor of fruits, which in turn affect the acceptance of fruits by consumers. Sugar is not only the carbon source and energy source of plants, but also acts as the signal molecule involved in the regulation of embryo formation, seed germination, fruit vegetative growth and reproductive growth during fruit growth. The soluble sugars in fruit are mainly sucrose, fructose, glucose and sorbitol, while the insoluble sugar is mainly starch. The changes of sugar synthesis, transport, metabolism and content during fruit development and ripening are affected by enzymes, genes, transcription factors, transporters, phytohormones and environmental conditions. Among them, phytohormones that regulate sugar metabolism during fruit development and ripening mainly include abscisic acid (ABA), auxin, ethylene (ETH), gibberellins (GA), brassinosteroids (BR), salicylic acid (SA), jasmonic acid (JA) and melatonin (MT), etc. In addition, fruit color is one of the key characteristics of fruit quality, which is crucial to the nutritional and commercial value of fruits, and is mainly affected by anthocyanin and carotenoid accumulation or chlorophyll degradation. Meanwhile, there is a complex relationship between sugar metabolism and the synthesis of anthocyanins and carotenoids. In this study, it reviews the role of sugar metabolism and its signal transduction mechanism during fruit development and ripening, and introduces the relationship between sugar signal transduction mechanism and the regulation of hormones and pigments, to provide important theoretical basis for fruit quality change and postharvest storage. Furthermore, the future research direction is prospected in order to promote the related researches in the field of sugar metabolism during fruit growth and development.